Tolerability, adverse events and compliance to glatiramer acetate in 28 patients with multiple sclerosis using the drug continuously for at least six months Tolerabilidade, eventos adversos e aderência ao acetato de glatiramer em 28 pacientes com esclerose múltipla usando a droga continuamente por pelo menos seis meses - Ana Patricia Perez Fiore; Yara Dadalti Fragoso (Arquivos de Neuro-Psiquiatria)
AIM: To assess tolerability, adverse events and compliance to treatment with glatiramer acetate in multiple sclerosis. METHOD: Review of patient records and individual interviews. RESULTS: 30 individuals residing in the coastal region of the State of São Paulo who had been in use of glatiramer acetate for at least 6 months were identified. From this group, 28 individuals came to regular consultations and were individually assessed, their complaints being noted down in confidential records. Ten patients reported systemic reactions to the drug. Four of them stopped the medication due to such reactions. Eight patients reported local reactions to the injections. Compliance with injections was achieved, although three patients reported forgetting the injection on a few days. CONCLUSION: We noticed a higher level of systemic adverse events in our patients than in reports in the literature. OBJETIVO: Avaliar tolerância, eventos adversos e aderência ao tratamento com acetato de glatiramer em esclerose múltipla. MÉTODO:Revisão de prontuários de pacientes e entrevistas individuais. RESULTADOS: 30 indivíduos residentes na região do litoral do Estado de São Paulo, que fizeram tratamento com acetato de glatirâmer por pelo menos 6 meses foram identificados. Deste grupo, 28 indivíduos compareceram a consultas regulares e foram avaliados individualmente, sendo suas queixas anotadas em prontuário confidencial. Dez pacientes relataram reações sistêmicas à droga. Quatro deles suspenderam o tratamento devido às reações. Oito pacientes relataram reação local às injeções. Aderência às injeções foi obtida, embora três pacientes admitam ter esquecido a injeção alguns poucos dias. CONCLUSÃO: Observamos um índice maior de reações sistêmicas em nossos pacientes do que o relatado na literatura.